Quaerens = searchings = paghahanap Filipino essays in medieval studies - Ocampo, Ma. Liza Ruth A.; Miroy, Jovino G. (UST Publishing House, 2008)
"This initial collection of Filipino Papers in Medieval studies proves that there are still some of us in Filipino letters who believe in the value of reading the Ancient texts and reading them slowly. It also demonstrates that we have been doing Medieval Studies for quite some time. Legend has it that Horacio de la Costa was a great advocate of Medieval Studies, and has made sure that libraries at the Ateneo de Manila be well stocked with sources on the Middle Ages. It will take another set of studies to document the beginnings of Medieval Studies in our country and to outline the contours of its development. For now, we offer these heretofore isolated forays into Medieval Studies in order to provide readers a cornucopia of essays that they can use either in their persona, explorations or in their history, philosophy, theology, and literature classes. These essays are not the apogee of Medieval Studies in the Philippines. It is prima facie evidence that Medieval Studies has been done and is being done on our intellectual landscape."--Back cover.